Magnitude of bycatch of Hippocampus patagonicus, an endangered species, in trawl fisheries in Southeast and South Brazil - Silveira, Rosana Beatriz; Vidal, Marcelo Derzi; Silva, José Rodrigo Santos (Frontiers in Marine Science, 2023)
One of the biggest threats to the world’s fish stocks is trawling with indiscriminate capturing of non-target organisms, typically referred to as bycatch. Some species of seahorses are globally threatened and are often targets caught as bycatch. The aim of this work is to describe the magnitude of bycatch of the Patagonian seahorse Hippocampus patagonicus (Sygnathidae) in trawling fisheries in the Southeast and South Brazil. Between 2016 and 2018 we monitored the catch of five trawling vessels off the coast of Rio de Janeiro and Sao Paulo. A total of 2,041 individuals of H. patagonicus were captured, 1,183 males and 858 females. They were evaluated as for injuries suffered during dragging. The average rate of body damage was 33%. Based on the individuals captured and the analysis of on-board maps, an average CPUE of 3.36 with a standard deviation of 5.95/ind./day/vessel was estimated for the study area, extrapolating an incidental removal of 2,282,515 individuals per year, or 9,427 metric tons of seahorses, along the South and Southeast Brazil, where 3700 trawlers operate, an area recognized as the geographic distribution of H. patagonicus in Brazil